let F : [ 0 , π ] → R be a smooth function with F ( 0 ) = F ( π ) = 0
You're given that ∫ 0 π ( F ( x ) ) 2 d x = 1
find the minimum value of ∫ 0 π ( d x d F ) 2 d x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
nice solution!
This is easily done using Fourier analysis. Since F is a smooth function on [ 0 , π ] , we can write F and F ′ as the convergent series F ( x ) = n = 1 ∑ ∞ a n sin n x F ′ ( x ) = n = 1 ∑ ∞ n a n cos n x Since ∫ 0 π sin m x sin n x d x = ∫ 0 π cos m x cos n x d x = 2 1 π δ m , n for all integers m , n ≥ 1 , where δ m , n is the Kronecker delta function δ m , n = { 1 0 m = n m = n we deduce from Parseval's Identity that 1 = ∫ 0 π F ( x ) 2 d x = 2 1 π n = 1 ∑ ∞ ∣ a n ∣ 2 ∫ 0 π F ′ ( x ) 2 d x = 2 1 π n = 1 ∑ ∞ n 2 ∣ a n ∣ 2 Since n = 1 ∑ ∞ n 2 ∣ a n ∣ 2 ≥ n = 1 ∑ ∞ ∣ a n ∣ 2 it follows that the minimum value of ∫ 0 π F ′ ( x ) 2 d x is 1 , and this minimum value is achieved with a n = π 2 δ n , 1 , so that F ( x ) = π 2 sin x .
Same approach! Just to confirm, the convergence is absolute, right?
Problem Loading...
Note Loading...
Set Loading...
Let m = max ∣ F ∣ and G ( x ) = d x d F .
First let's prove a lemma, namely that m > π 1 .
Observe that since F 2 ( x ) ≤ m 2 , then ∫ 0 π F 2 d x = 1 ≤ ∫ 0 π m 2 d x = m 2 π .
The only way equality can occur is if F ( x ) = m = π 1 for all 0 ≤ x ≤ π . However, this is impossible, given that F ( 0 ) = F ( π ) = 0 and F is a smooth function. Hence m 2 π > 1 , so m is strictly greater than π 1 . □
So let's prove the theorem, that the minimum value of ∫ 0 π G 2 d x is 1 . ∫ 0 π G 2 d x = m 2 π − 1 1 ∫ 0 π G 2 d x ∫ 0 π ( m 2 − F 2 ) d x
By the Cauchy-Schwarz Inequality for integrals, we have: ∫ 0 π G 2 d x ∫ 0 π ( m 2 − F 2 ) d x ≥ ( ∫ 0 π ∣ G ∣ m 2 − F 2 d x ) 2 Now let a 0 = 0 , a n = π and let a 1 , a 2 , a 3 . . . a n − 1 be the local minimum/maximum points of F . Without loss of generality, let's assume that G ( x ) ≥ 0 for 0 ≤ x ≤ a 1 . So in general, for a 2 k ≤ x ≤ a 2 k + 1 , G ( x ) ≥ 0 and F is increasing; while for a 2 k − 1 ≤ x ≤ a 2 k , G ( x ) ≤ 0 and F is decreasing. As a corollary, for all k , we have F ( a 2 k ) < F ( a 2 k + 1 ) > F ( a 2 k + 2 ) .
Therefore, the last integral can be rewritten as follows: ∫ 0 π ∣ G ∣ m 2 − F 2 d x = k = 0 ∑ ⌊ ( n − 1 ) / 2 ⌋ ( ∫ a 2 k a 2 k + 1 G m 2 − F 2 d x ) + k = 1 ∑ ⌊ n / 2 ⌋ ( ∫ a 2 k − 1 a 2 k ( − G ) m 2 − F 2 d x ) = k = 0 ∑ ⌊ ( n − 1 ) / 2 ⌋ ( ∫ F ( a 2 k ) F ( a 2 k + 1 ) m 2 − y 2 d y ) + k = 1 ∑ ⌊ n / 2 ⌋ ( ∫ F ( a 2 k ) F ( a 2 k − 1 ) m 2 − y 2 d y ) Let H ( c , x ) = ∫ c x m 2 − y 2 d y . Note that d x d H is positive. Therefore, if c ≤ x then H ( c , x ) ≥ 0 and vice versa.
Let s be the minimum value of F and t be the maximum value of F on 0 ≤ x ≤ π . By our assumptions about the local minima/maxima, t = F ( a 2 p + 1 ) and s = F ( a 2 q ) for some p , q . Now consider all the intervals [ F ( a 2 k ) , F ( a 2 k + 1 ) ] . I will leave it as an exercise to prove that the union of these intervals is the entire interval [ s , t ] . Therefore, k = 0 ∑ ⌊ ( n − 1 ) / 2 ⌋ ( ∫ F ( a 2 k ) F ( a 2 k + 1 ) m 2 − y 2 d y ) ≥ ∫ s t m 2 − y 2 d y = H ( s , t ) By similar reasoning, we can show that: k = 1 ∑ ⌊ n / 2 ⌋ ( ∫ F ( a 2 k ) F ( a 2 k − 1 ) m 2 − y 2 d y ) ≥ ∫ s t m 2 − y 2 d y = H ( s , t ) Putting the two sums together, we get: ∫ 0 π ∣ G ∣ m 2 − F 2 d x ≥ 2 H ( s , t ) By definition of m , either s = − m or t = m . If s = − m , we know that t ≥ 0 because F ( 0 ) = 0 . Then H ( s , t ) = H ( − m , 0 ) + H ( 0 , t ) ≥ H ( − m , 0 ) = 4 m 2 π (the last equality is by definition of H ). Similarly if t = m , we also get H ( s , t ) ≥ 4 m 2 π . Therefore, ∫ 0 π ∣ G ∣ m 2 − F 2 d x ≥ 2 m 2 π
Putting it all together gives us: ∫ 0 π G 2 d x ≥ m 2 π − 1 1 ( ∫ 0 π ∣ G ∣ m 2 − F 2 d x ) 2 ≥ m 2 π − 1 1 ( 2 m 2 π ) 2 = 4 ( m 2 π − 1 ) m 4 π 2
Now let's set a boundary on 4 ( m 2 π − 1 ) m 4 π 2 :
4 ( m 2 π − 1 ) m 4 π 2 = 1 + 4 ( m 2 π − 1 ) ( m 2 π − 2 ) 2 ≥ 1 + 0 = 1
(Note that we need the fact that m 2 π > 1 here).
Therefore, ∫ 0 π G 2 d x ≥ 1
This value is achieved when F ( x ) = π 2 sin ( x ) .
QED